Comparison of the overnight metyrapone and glucagon stimulation tests in the assessment of secondary hypoadrenalism. (10th April 2013) - Cegla, Jaimini; Jones, Ben; Seyani, Lata; Papadoulou, Deborah; Wynne, Katie; Martin, Niamh M.; Meeran, Karim; Chapman, Richard; Donaldson, Mandy; Goldstone, Anthony P.; Tan, Tricia
Summary Objective The insulin tolerance test (ITT) is contraindicated in a proportion of patients with suspected ACTH deficiency. The aim of this study was to investigate the diagnostic accuracy of the glucagon stress test (GST) compared with the overnight metyrapone test (OMT) in patients with contraindications to ITT. Design This was a prospective comparison of the GST to the OMT in patients with suspected ACTH deficiency and contraindications to the ITT. The OMT was used as the standard for comparison. The study was conducted at two tertiary referral centres for pituitary disease. Patients Seventy‐eight patients underwent contemporaneous OMT and GST of whom 61 had sufficient suppression of cortisol during the OMT to be included in the comparison. Forty had suffered traumatic brain injury, 36 had organic pituitary disorders and two were classified as 'other'. Measurements ACTH sufficiency was defined as 0800h 11‐deoxycortisol ≥ 200 nmol/l on OMT and peak cortisol ≥ 440 nmol/l on GST, as per local reference ranges. Results There was significant discrepancy between the proportion of patients diagnosed with ACTH deficiency using the OMT (39%) and GST (89%). From our data, a GST peak cortisol cut‐off of ≥350 nm provides the combination of optimal sensitivity (71%) and specificity (57%), compared with a higher sensitivity (88%) but poor specificity (11%) using a cut‐off of ≥440 nm. Conclusions The GST should be used with caution as a diagnostic test of ACTH reserve. The OMT should be used in preference to the GST to assess the hypothalamic pituitary adrenal axis where ITT is contraindicated.